Right ventricular long axis strain—validation of a novel parameter in non-ischemic dilated cardiomyopathy using standard cardiac magnetic resonance imaging. Issue 7 (July 2016) - Arenja, Nisha; Riffel, Johannes H.; Djiokou, Charly Noel; Andre, Florian; Fritz, Thomas; Halder, Manuel; Zelniker, Thomas; Kristen, Arnt V.; Korosoglou, Grigorios; Katus, Hugo A.; Buss, Sebastian J.
Abstract: Purpose: Right ventricular longitudinal axis strain (RV-LAS) is a simple measure of RV longitudinal function. The purpose of this study was the evaluation of its diagnostic performance in non-ischemic dilated cardiomyopathy (NIDCM) and the determination of reference values in controls. Methods: 217 NIDCM patients and 200 healthy controls were analysed retrospectively regarding the diagnostic performance of RV-LAS using receiver operating characteristic curves in comparison with RV ejection fraction (RVEF), tricuspid annular plane systolic excursion (TAPSE) and global longitudinal strain (RV-GLS). Hereby, four different approaches were evaluated to assess RV-LAS based on different reference points. RV-LAS LVapex/mid was defined as the change in distance between the LV apex and the middle of a line connecting the origins of the tricuspidal valve leaflets in systole and diastole. The ethical approval was obtained in all participants. Results: NIDCM and controls were 48 years in mean. Controls were equally gender distributed, while the proportion of men with NIDCM was higher with 77%. Among the four approaches RV-LAS LVapex/mid provided the highest diagnostic performance for discrimination between NIDCM and controls (AUC = 0.94). Of all RV functional parameters RV-LAS LVapex/mid preformed significantly better than RVEF (delta AUC = 0.05; p = 0.003), TAPSE (delta AUC = 0.23; p < 0.0001) and RV-GLS (delta AUC = 0.31; p < 0.0001). A significant correlation was found between RV-LAS LVapex/mid and RVEF ( r  = −0.65; p < 0.0001). The reference mean values for RV-LAS LVapex/mid were −17.4 ± 3.5 for men and −18.5 ± 3.7 for women. Conclusion: RV-LAS showed better diagnostic accuracy for RV dysfunction than RVEF, TAPSE and RV-GLS. Furthermore, it has a rapid accessibility and low intra- and interobserver variability.